Experimental study of a direct solar drying process with a thermal storage System using latent heat - ZINE, Ali; BENSEDDIK, Abdelouahab; SAIM, Rachid; LAOUINI, Abdeldjalil; OUCIF KHALED, M Tayeb (Sousse - Tunisia, 2024)
In this study, we designed a direct solar dryer at the Research and Development Unit for Renewable Energies in Ghardaia to dry tomatoes. A phase change material was used to store excess heat and utilize it when the sun was absent to increase the dryer's efficiency. The obtained results from the drying kinetics were modeled. The results showed that the Page model was the best model to predict the drying kinetics of tomatoes in the studied dryer (𝑅2=0.99946,𝑀𝑆𝐸=0.00911,𝜒=8.2914𝐸−5 ). Additionally, the use of the phase change material increased the dryer’s temperature in the absence of sunlight compared to the dryer without the phase change material. The effective moisture diffusion value in the tomato slices was 5.12586−9(𝑚2𝑠⁄). الملخص قمنا في هذه الدراسة بتصميم مجفف شمسي مباشر بوحدة البحث والتطوير للطاقات المتجددة بغرداية لتجفيف الطماطم. تم استخدام مادة متغيرة الطور لتخزين الحرارة الزائدة واستخدامها عند غياب الشمس لزيادة كفاءة المجفف. تم نمذجة النتائج التي تم الحصول عليها من حركية التجفيف. أظهرت النتائج أن نموذج بيج هو النموذج الأفضل للتنبؤ بحركية تجفيف الطماطم في المجفف المدروس
Intervention
Keywords: Solar Drayer; PCM; Drying Kinetics. Tomatoes; مجفف شمسي مباشر; حركية التجفيف; مادة ثنائة الطور; الطماطم